Electron microscopy study on antitumor efficacy of rutin and cisplatin combination treatment in ascites Dalton’s lymphoma-bearing mice - Prasad, Rajesh; Prasad, Surya Bali (Journal of Advanced Education and Sciences, 2026)
Cisplatin is a recognized cancer chemotherapeutic drug and its overall therapeutic efficacy is slowed down due to formation of several adverse side-effects in the host. Rutin, a naturally occurring flavonoid has proved to have many pharmacological properties. Some drugs when used in combination against cancers have proved to be much better in improving therapeutic efficacy as well as reducing alone drug induced toxicities in the hosts. Further, rutin-cisplatin combination treatment had been reported to show antitumor activity and histoprotective property in various models. The present study was focused on to evaluate antitumor efficacy of rutin-cisplatin combination treatment in ascites Dalton’s lymphoma (DL) bearing mice particularly by electron microscopy analysis. Results: Scanning electron microscopy (SEM) of the DL cells in combination treatment with rutin and cisplatin showed severe membrane deformities in DL cells compared to alone treatment such as fusion of cell membrane, membrane blebbing, cell shrinkage, membrane folding and loss in microvilli from the tumor cell surface which may contribute to cell death. Transmission electron microscopy (TEM) of the DL cells also showed severe changes in internal architecture of cell organelles such as mitochondrial membrane disruption, elongated mitochondria with thickened and disrupted mitochondrial cristae and formation of vacuoles in DL cells in combination treatment compared to alone treatment. Conclusion: The results obtained from SEM and TEM study showed that rutin-cisplatin combination treatment exerts more antitumor effect on DL cells compared to their alone treatment.